Challenges of geothermal energy development in East Afican countries: case of Djibouti geothermal projects - Ismail Mohamed, Kadra; Kassim, Salina (Academia Industry Network, 2024)
Geothermal energy development presents a promising opportunity for East African countries to address their growing energy needs while contributing to sustainable development. However, despite the region's abundant geothermal resources, several challenges hinder the successful exploitation of this potential. This study qualitatively assesses the challenges faced in geothermal energy development in East African countries, with a particular emphasis on Djibouti’s geothermal projects. Key challenges identified include the high upfront investment required for exploration and drilling, coupled with limited access to financing options, which are exacerbated by the region's nascent regulatory and policy frameworks. By analyzing Djibouti’s experience, this research underscores the need for comprehensive strategies that involve supportive policies, capacity building, international collaboration as well leveraging Islamic financial instrument to overcome these barriers. The findings offer valuable insights for policymakers, developers, and stakeholders aiming to unlock the potential of geothermal energy in Djibouti and the broader East African region, contributing to the region’s energy security and economic development.